Gender differences and stage-specific influence of parent–adolescent conflicts on adolescent suicidal ideation. (September 2017) - Chiu, Yu-Ching; Tseng, Chin-Yuan; Lin, Fu-Gong
Abstract: This study examined familial and peer related factors as predictors of suicidal ideation in school students. Total 2896 participants were included from Taiwan Youth Project released data, a longitudinal survey of adolescent suicidal ideation at ages 15, 18, and 20. Logistic regression analysis risk factors associated with adolescent suicidal ideation reveled differences during the developmental stages. After adjusted for psychological symptoms, effect of quarrels with parents on suicidal ideation lasts in early and middle stages; in the late adolescent stage, only cigarette or alcohol use remained significant. Girls who reported quarrels with parents had the highest level of suicidal ideation before age 18. Stage- and gender-specific differences may provide appropriate intervention strategies for parents and teachers preventing adolescent suicidal ideation. Highlights: Factors for suicidal ideation differ with adolescent stages. Familial and school factors dominate suicidal ideation at an early stage. Psychological symptoms account for more suicidal ideation risk in later stages. Impact of quarrels with parents on suicidal ideation lasts in early/middle stages. Girls quarreling with parents have the highest early-stage suicidal ideation risk.